L’IMPACT DE LA CULTURE DU COTON SUR LE DEVELOPPEMENT SOCIO-ECONOMIQUE : ETUDE DE CAS DE LA REGION DE KORHOGO, AU NORD DE LA COTE D’IVOIRE - Aïwa Aïwa Edmond (European Scientific Journal, ESJ, 2015)
Cotton cropping is one of the main sources of income of the Ivorian economy. It counts for less than 10% of the export incomes. Cotton is the third most important cash crop of the country after cocoa and coffee. Cotton cropping is the main economic resource in the savannah area although it has little relative importance at the national level. The fibre production average 100,000 tones per annum, of which 90% are exported. The present study deals with the impact of cotton cropping on socio-economic development by analysing the farmer agricultural incomes and their uses.